The Effect of Profitability, Sales Growth, and Leverage on Financial Distress in Indonesian Retail Companies - Oktaviani, Nadia; Zulvia , Yolandafitri (Manunggal Halim Jaya, 2026)
Financial distress is a situation in which a company's financial status has declined, potentially leading to bankruptcy. Companies experiencing financial distress often need to restructure their debt, sell assets, and liquidate their operations. This phenomenon is a significant issue for retail companies in Indonesia, particularly in the face of intense competition, shifting consumer behavior, and global economic pressures. Therefore, companies are required to maintain financial stability and improve operational performance to avoid the risk of financial distress and ensure business sustainability amid economic challenges. This study aims to provide empirical evidence on the effects of profitability, sales growth, and leverage on financial distress in retail companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The population in this study consisted of retail companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023, with a total research sample of 29 companies, determined using a purposive sampling method. The data was collected and processed using the Microsoft Excel 2019 program and IBM SPSS Statistics 22. The results of this study concluded that (1) profitability has a negative and significant effect on corporate financial distress, (2) sales growth has no effect on corporate financial distress, and (3) leverage has a positive and significant effect on corporate financial distress.